Professional soft competencies of future software engineers: key concepts - Vakaliuk, Tetiana A.; Kontsedailo, Valerii V.; Mintii, Iryna S. (Osvìtnìj vimìr (Online), 2020)
The conceptual apparatus was analyzed in the article and the interpretation of the basic concepts of different authors was considered. The analysis of scientific sources allowed to generalize the concept of “professional soft competencies” as follows: it is a set of non-specialized competencies that in one way or another relate to problem solving, interaction between people and are responsible for successful participation in the work process, high productivity and , in contrast to specialized competencies, not related to a specific area, equipment control and technical skills. They cover the following aspects of behavior: situational awareness, decision making, error management, interpersonal communication, and so on. In general, these competencies are important for software developers, as software development projects are organized on the basis of teams or groups, where software engineers make up the majority of the team.